Boron, copper and zinc supply by insertion tablets in the coffee orthotropic stem - Poltronieri, Yonara; Martinez, Herminia Emilia Prieto; Clemente, Junia Maria; Ferreira, Aline de Oliveira (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to evaluate the viability supply of boron (B), copper (Cu) and zinc (Zn) through salts tablets implanted in Coffea arabica stem. The experiment was carried out using a coffee plantation in a randomized block design with 6 treatments and 4 replicates. The treatments were different supply routes as described next: without supply of B, Cu and Zn; foliar sprays with boric acid, copper oxychloride and zinc sulfate applied in 0.4% concentrations; tablet containing B salts; tablet containing Cu salts; tablet containing Zn salts and tablet containing B, Cu and Zn salts. Tablets were introduced in the sapwood of orthotropic branches to 10 cm above the soil surface. Both forms of supply, foliar sprays and tablets trunk insertion are efficient supply B, Cu and Zn on coffee, thus proved to be a promising way of supplying these micronutrients.